Construção participativa de estratégias para a transição agroecológica em assentamento de reforma agrária - Lopes, Angelo da SiIva (2007)
The verification of the problems caused by the green revolution, as much to the man, as for the environment as a whole, made the need of developing more maintainable systems of production farming. In order to answer to that new demand is that ecological based agriculture has emerged, which congregates all of the styles of the called alternative agricultures to the model of conventional production, whose theoretical-scientific base is found in the agroecology. Starting from the farmers' motivation to the entrance in the complex process of agroecological transition, a new lack emerges, the one of the establishment of strategies to aid new conversion process. However, development projects that were accomplished under the logic diffusion of the green revolution, disrespecting the opinion of those who would be the actors of the process, the farmers, counted with great failures. The present research, was ruled by developing the strategies of agroecological transition, under a participative optics, elevating the farmers from mere study objects, to the actors in the technological process. To achieve such objective, one worked with a group of settled farmers, which produce now in a conventional production system, but manifested the intention of converting to a ecological based production system. Techniques of participative research were used, gathering information directly from the subjects, besides auxiliary processes that followed the methodology of the Fast Rural Diagnosis and Participation (DRP). As result, that work obtained a plan of strategies for the agroecological transition, which show to be contextualized with the farmers' reality, what can be considered as positive point, glimpsing its implantation.